The Gathering of Intentions: A History of Tibetan Buddhist Tantra, by Jacob P. Dalton. (30th December 2018) - van Schaik, Sam
Abstract : The Gathering of Intentions: A History of Tibetan Buddhist Tantra, by Jacob P. Dalton. Columbia University Press, 2016. 272pp. Hb. $60.00 (cloth), ISBN-13: 9780231176002.